Contract Teachers in India - Goyal, Sangeeta; Pandey, Priyanka (Taylor and Francis, 2013)
In this paper, we use non‐experimental data from government schools in Uttar Pradesh and Madhya Pradesh, two of the largest Indian states, to present average school outcomes by contract status of teachers. We find that contract teachers are associated with higher effort than civil service teachers with permanent tenures, before as well as after controlling for school fixed effects. And higher teacher effort is associated with better student performance after controlling for other school inputs and student characteristics. Given that salaries earned by contract teachers are one‐fourth or less of civil service teachers, contract teachers may be a more cost‐effective resource. However, contracts ‘as they are’ appear weak. Not only do contract teachers have fairly low average effort in absolute terms, but those who have been on the job for at least one full tenure have lower effort than others who are in the first contract period.